Patterns of Failure in Patients With Head and Neck Squamous Cell Carcinomas of Unknown Primary Treated With Chemoradiotherapy. (1st June 2020) - Dhouib, Fatma; Bertaut, Aurélie; Maingon, Philippe; Siala, Wicem; Daoud, Jamel; Aubignac, Léone; Lestrade, Laetitia; Crehange, Gilles; Vulquin, Noemie
Background: To evaluate the patterns of failure in patients treated for head and neck carcinoma of unknown primary and to discuss treatment practices concerning radiotherapy target volumes definition and dose prescription. Methods: Eleven patients presenting a locoregional recurrence after head and neck carcinoma of unknown primary treatment with curative-intent radiochemotherapy performed between 2007 and 2017 in the departments of radiation oncology of 2 French cancer institutes. Images of the computed tomography scan or the magnetic resonance imaging performed at the time of the recurrence were fused with those of the simulation computed tomography scan to delimit a volume corresponding to the recurrence and to define the area of relapse compared to the volumes treated. Results: Irradiation was unilateral in 6 cases and bilateral in 5 cases. The median time to onset of recurrence was 7.24 months (extreme 3-67.7 months). Six patients had only a neck node recurrence, 3 had a neck node and subsequent primary recurrence, and 1 had only a median subsequent primary recurrence. Only 1 patient had synchronous distance progression to local recurrence. All neck node recurrences were solitary and ipsilateral. The subsequent primary recurrences were in the oropharynx in 3 cases and in the contralateral oral cavity in one case. All neck node recurrences were into the irradiated volume. The subsequent primary recurrences were either within or in border of the irradiated volumes. The median of the mean dose, received by neck node recurrences, was 69.9 Gy and that of the mean dose, minimum dose, maximum dose, and dose received by 95% of the volume of recurrence was 66.7 Gy. For the primary relapses, the median of the mean dose was 52.1 Gy and that of the mean dose, minimum dose, maximum dose, and dose received by 95% of the volume of recurrence was 39.9 Gy. Conclusions: All local nodal recurrences occurred at sites that received high radiotherapy doses and doses received by sites of eventual failure did not vary significantly from sites that remain in control.